The updated understanding of advanced maternal age - Xuan Ye; Philip N. Baker; Chao Tong (Fundamental Research)
The rising rates of pregnancies associated with advanced maternal age (AMA) have created unique challenges for healthcare systems worldwide. The elevated risk of poor maternal outcomes among AMA pregnancies is only partially understood and hotly debated. Specifically, AMA is associated with reduced fertility and an increased incidence of pregnancy complications. Finding a balance between global fertility policy, socioeconomic development and health care optimization ultimately depends on female fertility. Therefore, there is an urgent need to develop technologies and identify effective interventions. Support strategies should include prepregnancy screening, intervention and postpartum maintenance. Although some reviews have considered the relationship between AMA and adverse pregnancy outcomes, no previous work has comprehensively considered the long-term health effects of AMA on mothers. In this review, we will begin by presenting the current knowledge of global health issues associated with AMA and the effects of advanced age on the female reproductive system, endocrine metabolism, and placental function. We will then discuss physiological alterations, pregnancy complications, and long-term health problems caused by AMA.